Analysis of the risks of using e-cigarettes in pregnancy: an integrative review (Research, Society and Development, 2022)
This study aimed to analyze the risks of using electronic cigarettes during pregnancy. For this, an integrative literature review was developed, in the PubMed, CINAHL and Scopus databases, as well as, in the searched AskMEDLINE, in July 2022, using the terms “Electronic cigarettes”, “Vaping” and “Pregnant women”, in the English, Portuguese and Spanish languages – adapting them according to each database. 452 studies were found, published between 2017 and 2021, and of these, five were selected to compose the sample, after applying the selection criteria and full reading of the studies. As a result, we found that the use of electronic cigarettes during pregnancy can lead to reduced breastfeeding, low birth weight newborns, lower than adequate head circumference, neuromotor alterations and higher rates of hospitalization in intensive care units, in addition to other complications. Thus, it is imperative that the habit of smoking these cigarettes be discouraged and that further investigations be conducted to expand clarification on the subject.